Infant feeding guideline awareness among mothers living with HIV in North America and Nigeria - J. Craig Phillips; Josephine Etowa; Jean Hannan; Egbe B. Etowa; Seye Babatunde (BMC, 2020)
Abstract Background WHO guidelines recommend breastfeeding for mothers living with HIV adherent to antiretroviral therapy in countries where formula is not accessible. In Canada and the US, guidelines for mothers living with HIV recommend exclusive formula feeding. Awareness of national infant feeding guidelines and socio-cultural factors influence infant feeding choices that may result in an increased risk of vertical transmission of HIV. The purpose of this paper is to present factors associated with awareness of guidelines among Black mothers living with HIV. Data were derived from a survey conducted as part of a recent international study that examined infant feeding practices among Black women living with HIV in Ottawa, Canada; Port Harcourt, Nigeria; and Miami, Florida. Methods Participants (n = 690) from Port Harcourt (n = 400), Miami (n = 201), and Ottawa (n = 89) were surveyed on their awareness of infant feeding guidelines for mothers living with HIV. Data were collected between November, 2016 and March, 2018. Results Participants' mean ages were 34.3 ± 5.9 years. Across all sites, 15.4% (95% CI 13.2, 7.7) of mothers were NOT aware of their country's infant feeding guidelines. Cultural beliefs (OR = 0.133, p = 0.004, 95% CI 0.03, 0.53) and functional social support influenced infant feeding choices (OR = 1.1, p = 0.034, 95% CI 1.01, 1.20) and were statistically significant predictors of guideline awareness (Χ 2  = 38.872, p < .05) after controlling for age, years of formal education, marital status, and country of residence. As agents of functional social support, family members and health workers (e.g., nurses, physicians, social workers, other health care workers) influenced participants' awareness of infant feeding guidelines and guided them in their infant feeding choices. Conclusions Among participants, awareness of national infant feeding guidelines was associated with functional social support and cultural beliefs influenced infant feeding choices. Therefore, culturally adapted messaging via social supports already identified by mothers, including family relationships and health workers, is an appropriate way to enhance awareness of infant feeding guidelines. Ultimately, contributing to the global health goals of maternal health and reduced infant mortality.